2019
DOI: 10.1186/s12893-019-0610-9
|View full text |Cite
|
Sign up to set email alerts
|

Simulation as tool for evaluating and improving technical skills in laparoscopic gynecological surgery

Abstract: Background Simulation in laparoscopic surgery is nowadays recognized as a valid instrument for learning and training surgeons in different procedures. However, its role as evaluation test and self-assessment tool to verify basic surgical skills is still under discussion. Methods Thirty-three residents in obstetrics and gynecology at University of Pisa, Italy were recruited, and they received a simulation program consisting of 5 tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 23 publications
(24 reference statements)
2
28
1
Order By: Relevance
“…The teaching of surgical techniques and surgery simulation gave rise to the need for mechanisms to evaluate the procedure, and OSATS has been widely used in several surgical areas for skill evaluation 20 , 24 including thoracic surgery 17 . The global rating scale used in the present study, adapted from the OSATS, demonstrated an improvement in continuous assessment from steps 1 to 3, but only the scores assigned by examiner 2 were statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…The teaching of surgical techniques and surgery simulation gave rise to the need for mechanisms to evaluate the procedure, and OSATS has been widely used in several surgical areas for skill evaluation 20 , 24 including thoracic surgery 17 . The global rating scale used in the present study, adapted from the OSATS, demonstrated an improvement in continuous assessment from steps 1 to 3, but only the scores assigned by examiner 2 were statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Simulation is a powerful tool to improve own capacities for laparoscopy skills. [ 11 ] Postgraduates need opportunities for regular, deliberate practice on simulators under faculty guide with constructive developmental feedback. [ 12 ] The apprentice-tutor model of surgical training “see one, do one, teach one” has lost favor to a variety of simulation methods that, while improving the skills of trainee, has zero risk to patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our results and evidence found in the literature suggest that simulator based educational programs should be an adjunct in the curriculum of minimal-invasive surgery training. Although most available data on this subject occur from visceral surgery and gynecology (18), we believe that they hold true in thoracic surgery. Over a very short training period, our impression was that resident 3D orientation, hand coordination and trainee satisfaction improved.…”
Section: Integration In the Standard Cursus And Library For Preparati...mentioning
confidence: 92%